Analysis of Plant Productivity, Farmer Income and Availability of Supporting Infrastructure on Soybean Agribusiness Institutional Performance in East Java - Iwan Harsono; Luluk Fadliyanti; Baiq Saripta Wiji Mulawiani; Abdullah Usman; Abubakar Abubakar (Westscience Press, 2024)
This research investigates the dynamics of soybean agribusiness in East Java through the lens of crop productivity, farmer income, supporting infrastructure, and institutional performance. A sample of 150 participants representing diverse scales of farming and geographic regions was surveyed to gather insights. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed to analyze the relationships among variables. The study confirmed positive and significant associations between crop productivity and farmer income, supporting infrastructure and crop productivity, and supporting infrastructure and institutional performance. Discriminant validity was established, and model fit indices indicated the reliability of the proposed structural model. Hypothesis testing further validated the impact of the availability of supporting infrastructure, farmer income, and plant productivity on institutional performance. The findings offer practical insights for policymakers, farmers, and stakeholders to optimize soybean agribusiness in East Java.